2019
DOI: 10.21203/rs.2.12636/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MRI-based Radiomics of Rectal Cancer: Preoperative Assessment of the Pathological Features

Abstract: [EXSCINDED] Abstract Abstract Abstract Background This study aimed to evaluate the significance of MRI-based radiomics model derived from high-resolution T2-weighted images (T2WIs) in predicting tumor pathological features of rectal cancer.Methods A total of 152 patients with rectal cancer who underwent surgery without any neoadjuvant therapy between March 2017 and September 2018 were included retrospectively. The patients were scanned using a 3-tesla magnetic resonance imaging, and high-resolution T2WIs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Radiomic analysis has been successfully utilized to predict survival outcomes in other diseases[ 12 - 14 ]. When integrated with the clinicopathologic features, the radiomics signature is superior to that of a single biomarker, in terms of prognostic value[ 15 - 17 ]. Hence, in the current study, the aim was to compare the predictive abilities, in terms of distant metastases and 3-year OS, of a radiomics signature and clinicoradiologic risk model in patients with RC.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomic analysis has been successfully utilized to predict survival outcomes in other diseases[ 12 - 14 ]. When integrated with the clinicopathologic features, the radiomics signature is superior to that of a single biomarker, in terms of prognostic value[ 15 - 17 ]. Hence, in the current study, the aim was to compare the predictive abilities, in terms of distant metastases and 3-year OS, of a radiomics signature and clinicoradiologic risk model in patients with RC.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with routine strategies using imaging methods, radiomics substantially improves disease diagnosis, tumor grading, and prognostic evaluation, providing a comprehensive guidance for treatment planning [16][17][18]. A previous study demonstrated that the SVM model showed good classification performance related to pathological features in patients with RC [13]. With continuous technology progress, the concept of "radiogenomics" has been widely applied in tumors recently.…”
Section: Discussionmentioning
confidence: 99%
“…All segmentations were checked by one senior radiologist (F.S., who had 12 years of experience in rectal MRI). and (4) higher-order statistics, encompassing transformed first-order statistics and texture features [13][14][15], e.g., logarithm, gradient, square, and wavelet transform. In the training cohort, inter-and intraclass correlation coefficients (ICCs) were determined to assess feature robustness.…”
Section: Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, radionics has been increasingly used in the evaluation of tumors. An MRI-based radiomics model has been used to distinguish tumors from benign tissues and reflect the histological characteristics of rectal cancer [ 30 , 31 ]. Hence, the present study explores the method of CRC LNM classification using MRI.…”
Section: Introductionmentioning
confidence: 99%